2018
DOI: 10.1016/j.ijnss.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IPMOE on nursing tasks in the medical ward: A time-motion study

Abstract: Introduction The In-patient Medication Order Entry System (IPMOE) was first implemented in the medical ward of Princess Margaret Hospital, Hong Kong. It was a local developed close-loop system including prescription, dispensing and administration modules. Evaluation on its impact on nursing tasks would be important for practice improvement and subsequent system enhancement. Objective The study was conducted to quantify the nursing times across medication-associated task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…One observation study out of eight measuring efficiency (12.5%) found that the average number of medication tasks reduced by 51.2% after eMAR implementation. 47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One observation study out of eight measuring efficiency (12.5%) found that the average number of medication tasks reduced by 51.2% after eMAR implementation. 47…”
Section: Resultsmentioning
confidence: 99%
“…25 Two studies did not find a significant time difference using eMAR versus paper MAR. 47,48 Two articles reported a 27.4 and 42.0% respective increase in medication administration time after eMAR implementation. 36,45 One study found nursing time on medication tasks outside of drug rounds increased by 36.1% after MAT implementation.…”
Section: Task Timementioning
confidence: 99%
“…The direct observation method was used to examine a range of technologies in relation to nursing work; a persistent theme was examination of how nurses spent their time. Most common was examination of EMM or physician ordering systems (Ampt & Westbrook, ; Asaro & Boxerman, ; Dwibedi et al, , ; Leung, Chan, Wong, & Law, ; Poon et al, ; Reed et al, ; Westbrook et al, ; Yen et al, ). Next most common was examination of nurses' clinical documentation (Ballermann, Shaw, Arbeau, Mayes, & Noel Gibney, ; Banner & Olney, ; Hurst, ; Ravat et al, ; Schachner et al, ; Wong et al, ) and EMR (Chung et al, ; Hakes & Whittington, ; Korst, Eusebio‐Angeja, Chamorro, Aydin, & Gregory, ; Read‐Brown et al, ; Roumeliotis et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Speed and accuracy are critical to capture frequent short events in a reliable way. One solution was to focus data collection on a single nursing activity related to the technology, for example medication administration was a common focus (Ampt & Westbrook, ; Ballermann et al, ; Cornell et al, , ; Dwibedi et al, , ; Leung et al, ; Reed et al, ; Westbrook et al, ). But the data show this single nursing care activity can involve going to multiple locations, obtaining many types of supplies and information, and communicating with patients, their companions and other clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of electronic medication administration records reduced treatment time. The research stated that IPMOE significantly reduced nursing time from 61.7 to 29.81 28 . The implementation of eMAR had an effect on improving patients' care and efficacy 6 .…”
Section: Nursing Time and Selfcarementioning
confidence: 97%